Evaluation of a telehealth training package to remotely train staff to conduct a preference assessment. Issue 2 (16th January 2017) - Higgins, William J.; Luczynski, Kevin C.; Carroll, Regina A.; Fisher, Wayne W.; Mudford, Oliver C.
Abstract : Recent advancements in telecommunication technologies make it possible to conduct a variety of healthcare services remotely (e.g., behavioral‐analytic intervention services), thereby bridging the gap between qualified providers and consumers in isolated locations. In this study, web‐based telehealth technologies were used to remotely train direct‐care staff to conduct a multiple‐stimulus‐without‐replacement preference assessment. The training package included three components: (a) a multimedia presentation; (b) descriptive feedback from previously recorded baseline sessions; and (c) scripted role‐play with immediate feedback. A nonconcurrent, multiple‐baseline‐across‐participants design was used to demonstrate experimental control. Training resulted in robust and immediate improvements, and these effects maintained during 1‐ to 2‐month follow‐up observations. In addition, participants expressed high satisfaction with the web‐based materials and the overall remote‐training experience.